IMPLEMENTASI KERJA SAMA PEMERINTAH DAN SWASTA DALAM PEMBANGUNAN INFRASTRUKTUR SEKTOR AIR MINUM DI INDONESIA - Bahtiar Rifai (Jurnal Ekonomi dan Pembangunan, 2025)
It has widely recognized how Public Private Partnership (PPP) contributes in infrastructure provision. Many countries have applied PPP for several reasons, ranging from limitation of government’s budget to the professionalism of private sector in developing and managing infrastructures. PPP infrastructure has been implemented in Indonesia since 1990s, and implemented initially on toll road and electricity sectors. Water as the basic infrastructure supporting development has limited private involvement compare to other sectors. Most of water services are provided and operated by Local Government Owned Enterprises (BUMD) which face several constraints to achieve better performance. This article based on field study in 2013 and conducted in three provinces such as: East Java, Banten and Jakarta. Primary and secondary data were used to analyse PPP implementation in water sector, particularly for characteristics, achievements, problems and challenges PPP. Primary data collected through in-depth interview with key institutions and Focus Group Discussion (FGD) representing stakeholders. Using development economics, public economics and institutional economics approaches, the result explained through descriptive qualitative analysis. The finding shows that water PPP has been implemented in various ways. The longest period for PPP has been undertaken by Jakarta Province through PAM Jaya cooperated with AETRA and Palyja Companies. In fact, private involvement on water provision in Jakarta haven’t been significantly improving to the company and service performances due to the lack of management and limited barganing position of PAM Jaya in the contract agreement. Meanwhile ideal showcase of water provision is Tangerang Regency along with PT AETRA Air Tangerang. Unfortunately this model tends pure private investment than in PPP implementation. Moreover, the biggest project (based on investment value) will be located in East Java province and it hasn’t started yet because institutional and administrative problems have been hampering on the PPP’s preparation process since it initiated.